TINGKAT STRES DENGAN KECUKUPAN PEMBERIAN ASI PADA IBU MENYUSUI DI RUMAH SAKIT SAKINA IDAMAN YOGYAKARTA - Anita Liliana; Endang Nurul Syafitri (Jurnal Ilmu Keperawatan Maternitas, 2022)
Background: Breast milk production can be influenced by several factors and one of them is psychological factor. Postpartum mothers may experience emotional disorders such as stress that can reduce the stimulation of the prolactine hormon which eventually it inhibits the production of breast milk.Objective : to find out whether there is a relationship between stress level and the adequacy of providing breast milk for breastfeeding mothers at Sakina Idaman Hospital.Research Methods : This study used a cross sectional design consisting of 42 respondents who were selected using a purposive sampling method. A questionnaire was implemented to conduct this study and it tested using the chi square test.Results : Univariate analysis showed that most respondents who did not experience stress were 36 people (85.7%), while most of the respondents considered sufficient in breastfeeding were 37 people (88.1%). The bivariate analysis result showed that there was a relationship between stress level and the adequacy of providing breast milk for breastfeeding mothers at Sakina Idaman Hospital with P = 0.002 (p<0.05).Conclusion : There is a Relationship between stress level and adequacy of providing breast milk for breastfeeding mothers at Sakina Idaman Hospital.